An empirical investigation on the capital structure determinants of companies listed in the Greek stock exchange - Παπαδόπουλος, Δημήτριος Λ.; Χαραλαμπίδης, Δημήτριος Π. (SPOUDAI Journal of Economics and Business, 2005)
This paper’s title is “An Empirical Research on the Capital Structure Determinants of Companies listed in the Greek Stock Exchange”. The paper investigates the capital structure determinants of companies listed at the Athens Stock Exchange. These companies exhibited low debt-to-equity ratio from 1998 until 2002. The industry debt-to-equity ratio (measured as the median debt-to-equity ratio of companies that operate in each industry) has the most significant effect on capital structure. Capital structure determinants of companies exhibiting low debt-to-equity ratio art; different from capital structure determinants of companies exhibiting high debt-to-equity ratio and there are some factors favoring the use of long-term, instead of short-term, borrowing. JEL Classification: G32